Peranan undang-undang dalam mempengaruhi amalan pemberian hibah di Malaysia - Nor Muhamad, Nasrul Hisyam (2018)
The practice of granting grants is one of the methods of estate planning that is gaining ground in the Muslim community in Malaysia. However, there are still disputes in the Court regarding the implementation of the grant. This is due to the absence of specific laws that provide for matters relating to granting of grants. Therefore, this study was conducted to identify the role of law in influencing grant practices. The data was collected through semi-structured interviews with experts in the field of estate planning. Interview data were analyzed using theme analysis. This study found that there are two main themes of the legal role: 'Guidelines' and 'Constraints'. These 'Guidelines' specify the appropriate methods for granting grants in accordance with Shariah and Civil requirements. While the laws relating to grants also impose restrictions on the grantor in granting the property to the beneficiary. This study proposes that a specific enactment or grant-related act should be drafted immediately to ensure that the granting practice is more systematic.